Elimination of Distortions in Static Magnetic Field Distribution Measurements - Andris, P.; Frollo, I. (Elektronika ir Elektrotechnika, 2008)
A new method for magnetic field distribution measurement distortions elimination using gradient-echo double measurement is introduced. To exclude phase distortion unwrapping algorithms or methods are used shortening the echo time of the measuring sequence. In the article the measurement acquisition was double repeated with different echo times and ratio of the both acquired and Fourier transformed data matrices was performed. The distortion due to phase periodicity was suppressed and also distortion due to background influence was eliminated. Method is applicable for all NMR scanners and is suitable for magnetic field distribution measurements. Ill. 3, bibl. 13 (in English; summaries in English, Russian and Lithuanian).